2018
DOI: 10.1159/000486017
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-10b Promotes Apoptosis via JNK Pathway in Clear Cell Renal Cell Carcinoma

Abstract: Background/Aims: To investigate the downregulation of microRNA (miR)-10b in clear cell renal cell carcinoma (ccRCC) and its mechanistic involvement in tumourigenesis. Methods: The relative expression of miR-10b in ccRCC samples were determined by real-time PCR. Exogenous expression and knockdown of endogenous miR-10b were performed by transfection with indicated plasmids into 786-0 cells. Cell proliferation was evaluated using Cell Counting Kit-8 assay. Cell apoptosis was analyzed by Annexin V/propidium iodide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…A study also showed that ABCC3 was able to contribute to hepatic cell growth (Fernandez‐Barrena et al, ). Consistently, miR‐10b has been investigated to be negatively associated with proliferation but positively correlated with apoptosis in clear cell renal cell cancer via the JNK pathway (Qin, Zhou, Teng, & Han, ). These supporting findings can help us explain why lung fibroblasts produced a lower degree of proliferation yet strengthened apoptosis in groups where miR‐448 expression was forced and ABCC3 expression was decreased.…”
Section: Discussionmentioning
confidence: 91%
“…A study also showed that ABCC3 was able to contribute to hepatic cell growth (Fernandez‐Barrena et al, ). Consistently, miR‐10b has been investigated to be negatively associated with proliferation but positively correlated with apoptosis in clear cell renal cell cancer via the JNK pathway (Qin, Zhou, Teng, & Han, ). These supporting findings can help us explain why lung fibroblasts produced a lower degree of proliferation yet strengthened apoptosis in groups where miR‐448 expression was forced and ABCC3 expression was decreased.…”
Section: Discussionmentioning
confidence: 91%
“…Studies have found that the activation of JNK signaling pathway can promote the production of vascular endothelial growth factor (VEGF) and matrix metalloproteinases (MMPs) by renal hyaluronic cell cancer cells, thus promoting tumor angiogenesis and remodeling of tumor microenvironment [30,31] , and these changes are conducive to the nutrient supply and metastasis of renal hyaluronic cell cancer cells. In addition, the activation of JNK can lead to the inhibition of apoptosis pathway, making renal hyaluronic cell cancer cells resistant to radiotherapy and chemotherapy [32,33] . Inhibition of JNK signaling pathway has become a research focus in the treatment of renal hyaluronic cell carcinoma [34] .…”
Section: Introductionmentioning
confidence: 99%